The Effect of Sociodemographic and Environmental Factors on Food Consumption Expenditure of the Urban Poor in Indonesia - Andi Kustanto (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
This paper aims to assess sociodemographic and environmental factors on food consumption expenditure of urban poor households in 33 provinces in Indonesia from 2008-to 2019. The data used in this study were sourced from the Central Bureau of Statistics. The method used is panel data econometrics with a fixed-effect model. This study provides empirical evidence that income per capita, population, family planning acceptors, and single residents have a positive and significant effect on the food consumption expenditure of the urban poor. Meanwhile, access to drinking water and improved sanitation has a negative and significant effect on food consumption expenditures for the urban poor. The policy implication that can be prioritized is to increase human capital investment because it will increase competence and employment opportunities so that the income earned can increase consumption. Increasing family planning acceptors is also needed to suppress the population growth rate because if there are additional family members, it will increase the consumption burden. This will impact increasing poverty if a level of welfare does not accompany it. In addition, access to drinking water and improved sanitation needs to be improved because they impact the health of the population in the long term